Counting women's work in the Philippines - Michael R.M. Abrigo; Kris Francisco-Abrigo (Philippine Institute for Development Studies (PIDS), 2019)
Men and women play important and complementary roles in the economy. However, the activities that they perform are often valued differently, if at all. In this study, we provide new estimates of the value of men and women's work in the Philippines using the National Transfer Account and the National Time Transfer Account frameworks. We find that once the value of unpaid home production is taken into account, the contribution of women is closer to parity relative to those by men, as opposed to using only the value of paid market work. This is despite the fact that home production activities, which are largely performed by women, are paid lower market wages. Additionally, we document a strong association between parental time and child schooling outcomes, which further emphasizes the contribution of unpaid housework in the economy.
Keywords: 330; Gender; Work; National Transfer Account; National Time Transfer Account